10 - Integrating Remote Sensing, GIS, Census, and Socioeconomic Data in Studying the Population–Land Use/Cover Nexus in Ghana: A Literature Update - Codjoe, Samuel Nii Ardey (Africa Development, 2007)
Land is a very important asset and a means to sustain livelihood. In the face of a rapidly growing global population, increase in technological capacity, and affluence, the earth’s land cover has been transformed, especially in developing countries. At the same time, social organisation, attitudes, and values have also undergone profound changes. In contemporary times, issues of sustainable development, pollution prevention, global environmental change and related issues of human-environment interaction have been a major concern globally. This concern has largely been sparked by the phenomenon of global warming and its consequences, which are threatening the very existence of humans on the surface of the earth. Remotely sensed data (mainly from aerial photographs and satellite images) in combination with Geographical Information Systems (GIS) have been observed to have potential scientific value for the study of population-environment interaction. This paper provides an account of how Remote Sensing, GIS, census (mainly population and agricultural) and socioeconomic (household, district and regional) survey data have been integrated in studying the population land-use/cover nexus in Ghana. It also identifies the major methodological challenges, and solutions.